Living with my folks: Emerging adults and their parents under one roof - Dor, Asnat (Advances in Social Sciences Research Journal, 2015)
This qualitative study focuses on Israeli emerging adults who live at home with their parents, and explores their feelings and thoughts as to the benefits and difficulties of the situation. Semi-structured open interviews were conducted with 18 Jewish non-religious emerging adults who live at home with their parents. Findings reveal that most of the participants experience ambivalence: the comfortable and secure living conditions at home and freedom from financial stress are accompanied by conflicts with their parents. Some participants chose this living arrangement for practical reasons, like saving money for later stages, while others chose to postpone dealing with adult responsibilities and enjoy being care for. The findings reveal that alongside the benefits, emerging adults face substantial challenges in living with their parents while they are on an extended journey toward adulthood. Keywords: Emerging adults, cohabitation with parents, parent-child conflict, parent-child relationship